Essays in industrial organization - Jain, Nilesh Kumar (New Delhi: Indian Statistical Institute, 2025)
This thesis contains three chapters on industrial organization, covering two distinct topics. Chapters 1 and 2 examine the impact of firm owner's corruption on the organization, while Chapter 3 analyzes the market dynamics of a two-sided newspaper market.\medskip The first chapter investigates the agency conflict that arises when the principal (the owner) of a firm is involved in corruption. A corruptible principal has an incentive to conceal his or her illegal activities, while the agent (CEO or manager), due to their information advantage, is in a position to monitor this corruption, thus creating an agency conflict. We show that such corruption leads to increased bureaucracy within the firm as the principal reduces information flow, provides lower incentive wages, and limits delegation to the manager. Furthermore, we analyze additional inefficiencies caused by such corruption, including the principal's incentive to distort talent by hiring a corruptible manager and to expropriate from minority shareholders.\medskip The second chapter investigates a screening mechanism through which a corruptible principal screens a manager when the manager's type (honest or corruptible) is private information at the time of hiring, and the corruptible manager can misappropriate funds from the firm. Our results show that if the potential for misappropriation by the manager is within an intermediate range, the principal can design a wage contract that ensures only a corrupt manager joins. This range increases if the reservation wage rises. We also demonstrate that the principal can completely offset the cost of the manager's misappropriation through a suitable wage contract, if these costs are not critically high.\medskip The third chapter extends the vertical differential framework by incorporating the advertisement side to analyze the two-sided newspaper market. Newspaper markets are highly concentrated, with most being monopolies or duopolies within a service area. Existing literature attributes this market concentration to the network effect, which arises because newspaper readers derive positive utility from advertisements, especially classifieds. We demonstrate that newspaper markets can also be concentrated due to endogenous investment in quality, particularly when quality improvements involve fixed costs like newsroom size. This reason more closely aligns with empirical evidence, which shows that market concentration persists even when classified ad revenues declined significantly due to online platforms like Craigslist. We also show that several different types of market and product configurations emerge depending on advertisement levels.
Corruptible Principal: Owner corruption makes firms bureaucratic -- Corruptible Principal: Screening of manager for collusion -- Newspaper Market: Impact of advertisement on quality and market structure
Thesis (Ph.D.) - Indian Statistical Institute, 2025
Includes bibliography
Guided by Prof. Prabal Roy Chowdhury
Keywords: Industry -- Economics